The Court of the Palms: A Functional Interpretation of the Mari Palace - Al-Khalesi, Yasin M. (1978)
Appendix (p. 71-81): Ron Glaeseman, Further Textual Evidence Describing the Architectural Features and Functional Aspects of the papāḫum at Mari.